Evolution of loyalty programs offered to customers and investors - Danuta Dziawgo (Financial Internet Quarterly, 2023)
The subject of this study is loyalty programs, The aim of the article is to draw attention to loyalty in the current economy, The purpose of the article is to examine the evolution of loyalty pro- grams offered to consumers and investors, The study will cover the issue of building a loyal base of clients and investors, To achieve the aim of the study in the article, analysis of the literature, description, comparison, desk research and case study methods were applied, The study pre- sents the author's definition and classification of loyalty programs, The research has demonstrat- ed that there is social acceptance for activities undertaken in the field of loyalty programs, Such loyalty programs tighten financial and non-financial links with stakeholders, At the same time, programs offered to consumers are evolving towards creating an emotional loyalty that reso- nates with consumers, In turn, programs offered to investors are evolving towards generating financial benefits only on the capital market, However, that means resigning from creating an investor as a consumer through the loyalty program, At the same time, the loyalty program is open to every investor, regardless of the country of origin and type of investor, It can be ex- pected that in the next stage of evolution these will be aware of their rights and environmentally sensitive stakeholders' attitudes and preferences will have to be taken into account to an in- creasing extent by the company
Keywords: D11; D21; E21; E22; G41; Q01; 330; loyalty program; consumers; financial investors